Stereoselectivity Switch in the Reduction of α-Alkyl-β-Arylenones by Structure-Guided Designed Variants of the Ene Reductase OYE1 - Crotti, Michele; Parmeggiani, Fabio; Ferrandi, Erica Elisa; Gatti, Francesco G.; Sacchetti, Alessandro; Riva, Sergio; Brenna, Elisabetta; Monti, Daniela (Frontiers in Bioengineering and Biotechnology, 2019)
Ene reductases from the Old Yellow Enzyme (OYE) family are industrially interesting enzymes for the biocatalytic asymmetric reduction of alkenes. To access to both enantiomers of the target reduced products, stereocomplementary pairs of OYE enzymes are necessary, but their natural occurrence is quite limited. A library of wild type ene reductases from different sources was screened in the stereoselective reduction of a set of representative α-alkyl-β-arylenones to investigate the naturally available biodiversity. As far as the bioreduction of the ethyl ketone derivatives concerns, the results confirmed the distinctiveness of the OYE3 enzyme in affording the reduced product in the (S) configuration, while all the other tested ene reductases from the Old Yellow Enzymes family showed the same stereoselectivity toward the formation of corresponding (R) enantiomer. A possible determinant role of the "hot spot" residue in position 296 for the stereoselectivity control of these reactions was confirmed by the replacement of Phe296 of OYE1 with Ser as found in OYE3. Further investigations showed that the same stereoselectivity switch in OYE1 could be achieved also by the replacement of Trp116 with Ala and Val, these experimental results being rationalised by structural and docking studies. Moreover, an additive effect on the stereoselectivity of OYE1 was observed when coupling the selected mutations in position 296 and 116, thus providing two extremely enantioselective variants of OYE1 (W116A-F296S, W116V-F296S) showing the opposite stereoselectivity of the wild type enzyme. Finally, the effects of the mutations in the bioreduction of carvone enantiomers were investigated as well.